2020
DOI: 10.1021/acs.energyfuels.0c01859
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Cathodes Based on Cobalt Nanoparticles Supported on Nitrogen-Doped Porous Carbon by Strong Electrostatic Adsorption for Advanced Lithium–Sulfur Batteries

Abstract: Energy demands have increased rapidly over the previous decades, leading to new innovations in the energy storage field. One of the candidates for advanced energy storage is the lithium-sulfur battery. This Li−S battery is advantageous for its relatively high volumetric and gravimetric energy density and affordability. However, the widespread use and manufacturing of Li−S batteries are hampered by accelerated capacity decay upon cycling due to volume changes at the cathode, a "shuttle effect" of soluble lithiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Most recently, it was observed that the Li–S batteries are a potential candidate for energy-storing devices due to their excellent energy density, indigenously available sulfur material, and low cost . Currently, researchers are focused on nanostructured composite materials and the development of battery design of Li–S batteries toward commercial application in electrochemical energy storage devices. Kang et al proposed a facile method for the synthesis of hierarchical porous activated carbon from coal having a high surface area of 3343 m 2 g –1 , which is beneficial for polysulfides while also increasing sulfur loading. As can be observed in Figure , the coal-derived hierarchical porous activated carbon had a high specific capacity of 1390 mAh g –1 at 0.05 C, as well as outstanding rate performances and cyclic stability.…”
Section: Coal-derived Activated Carbon As Electrode Materials For Li–...mentioning
confidence: 99%
“…Most recently, it was observed that the Li–S batteries are a potential candidate for energy-storing devices due to their excellent energy density, indigenously available sulfur material, and low cost . Currently, researchers are focused on nanostructured composite materials and the development of battery design of Li–S batteries toward commercial application in electrochemical energy storage devices. Kang et al proposed a facile method for the synthesis of hierarchical porous activated carbon from coal having a high surface area of 3343 m 2 g –1 , which is beneficial for polysulfides while also increasing sulfur loading. As can be observed in Figure , the coal-derived hierarchical porous activated carbon had a high specific capacity of 1390 mAh g –1 at 0.05 C, as well as outstanding rate performances and cyclic stability.…”
Section: Coal-derived Activated Carbon As Electrode Materials For Li–...mentioning
confidence: 99%
“…El-Kadri et al recently reported that ultrafine cobalt nanoparticles incorporated in a nitrogen-doped carbon composite allow for a high sulfur loading and considerably immobilize soluble lithium polysulfide (LPS) during battery cycling while increasing the electrochemical performance through catalytic effects …”
Section: Polar Composite Cathode Materialsmentioning
confidence: 99%
“…(b) Charge–discharge voltage profiles for the first 5 cycles of Co–BIDC/S at 0.1 C. The sulfur loading of Co–BIDC/S is 1.2 mg cm –2 . This figure was adapted with permission from ref . Copyright 2020 American Chemical Society.…”
Section: Polar Composite Cathode Materialsmentioning
confidence: 99%
See 2 more Smart Citations